HOLLOW INORGANIC PARTICLES AND METHOD FOR PRODUCING SAME
Patent Information
- Application Number
- JP2020123143
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-17
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2040-07-17
AI Technical Summary
【0013】 本発明によれば、空隙率が高いにも関わらず、強度の優れた中空無機粒子を提供することができる。 なお、ここに記載された効果は、必ずしも限定されるものではなく、本明細書中に記載されたいずれかの効果であってもよい。
Smart Images

Figure 0007645053000003 
Figure 0007645053000004 
Figure 0007645053000005
Abstract
Description
[Technical field]
[0001] The present invention relates to hollow inorganic particles and a method for producing the hollow inorganic particles. [Background technology]
[0002] Hollow inorganic particles are used in a wide range of fields, including as fillers, spacers, ceramic raw materials, resin improvers, adsorbents, electronic materials, semiconductor materials, paints, cosmetics, etc. In recent years, various technologies have been developed for the purpose of improving the performance of hollow inorganic particles and imparting characteristics according to various applications.
[0003] For example, Patent Document 1 describes a technology for producing hollow inorganic particles having inorganic particles present in the hollow portion by carrying out a coating step in which a polyorganosiloxane coating is formed on polymer particles containing a polyorganosiloxane polymer to obtain coated polymer particles, and a calcination step in which the coated polymer particles are calcined.
[0004] Patent Document 2 describes a technology for producing hollow polyorganosiloxane particles, which are characterized by having an average particle outer diameter of 1 to 15 μm and a hollow interior, by removing the organic resin particle component of composite particles, which are characterized by having a spherical shape or a shape in which small polyorganosiloxane protrusions are chemically bonded to the surface of the spherical particles, and the blending amount of polyorganosiloxane is 1 to 50 parts by weight per 1 part by weight of organic resin particles.
[0005] Patent Document 3 describes a technology for producing spherical metal compound hollow particles having voids inside the particles by heating spherical polymer-metal compound composite particles, which are characterized by having a core made of a polymer and a shell made of a metal compound selected from titanium compounds and / or silicon compounds. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2011-132087 A [Patent Document 2] JP 2014-162920 A [Patent Document 3] Japanese Patent Application Publication No. 6-142491 Summary of the Invention [Problem to be solved by the invention]
[0007] As mentioned above, various technologies are being developed for the purpose of improving the performance of hollow inorganic particles and imparting properties according to various applications, and for example, a method is used in which hollow inorganic particles are kneaded with materials such as resins and ceramics to create an air layer inside the material for the purpose of lowering the dielectric constant, lowering the refractive index, etc. In this case, in order to uniformly disperse the hollow inorganic particles in other materials, a force such as stirring and mixing is applied when kneading the material and the hollow inorganic particles, but this force causes the hollow inorganic particles to break, resulting in a problem that an air layer cannot be created within the material.
[0008] On the other hand, the thicker the shell is made in order to improve the strength of hollow inorganic particles, the lower the porosity becomes, and the inherent effect of creating an air layer inside the material is not achieved.
[0009] Therefore, a main object of the present technology is to provide hollow inorganic particles that have excellent strength despite having a high porosity. [Means for solving the problem]
[0010] That is, in this technology, first, The particle size distribution coefficient of variation is 10% or less. To provide hollow inorganic particles having a ratio of the thinnest part of the outer shell to the thickest part of the outer shell of 0.80 or more. The hollow inorganic particles according to the present technology can have an average particle outer diameter of 0.05 to 5 μm. The hollow inorganic particles according to the present technology can have a particle inner diameter / particle outer diameter ratio of 0.55 to 0.93. The hollow inorganic particles according to the present technology can have an outer shell composed of silica or organopolysiloxane. The hollow inorganic particles according to the present technology can have a water absorption rate of less than 2%. In the hollow inorganic particles according to the present technology, the proportion of hollow inorganic particles A having an average particle outer diameter of 0.1 to 5 μm can be less than 80% by weight of the total, and the proportion of hollow inorganic particles B having an average particle outer diameter smaller than that of hollow inorganic particles A can be more than 20% by weight of the total.
[0011] In this technology, next, a coating step of coating the core particles made of an organic polymer with a silicone-based compound is performed. a core particle removing step of removing the core particles; having In the coating step, Dispersant in core particle dispersion As a nonionic surfactant A dispersant addition step of adding a surfactant addition step of adding a cationic polymer surfactant after the dispersant addition step; The present invention provides a method for producing hollow inorganic particles, comprising the steps of: In the production method according to the present technology, in the coating step, the concentration of the cationic surfactant in the core particle dispersion after the surfactant addition step can be set to 0.05 to 5 g / L. The dispersant used in the production method according to the present technology can be a hydrophilic polymer.
[0012] Furthermore, the present technology can provide a low dielectric material using the hollow inorganic particles. Effect of the Invention
[0013] According to the present invention, it is possible to provide hollow inorganic particles having excellent strength despite having a high porosity. Note that the effects described here are not necessarily limited to those described herein, and may be any of the effects described in this specification. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a cross-sectional image diagram showing an example of a cross-sectional structure of a hollow inorganic particle 1 according to the present technology. [Diagram 2] FIG. 1 is a flow diagram of a method for producing hollow inorganic particles 1 according to the present technology. [Diagram 3] 2 is a cross-sectional microscope photograph of a hollow inorganic particle according to Example 1. [Figure 4] 3 is a cross-sectional microscope photograph of a hollow inorganic particle according to Example 2. [Diagram 5] 2 is a cross-sectional microscope photograph of a hollow inorganic particle according to Comparative Example 1. [Figure 6] 3 is a micrograph of hollow inorganic particles according to Comparative Example 2. [Figure 7] 13 is a micrograph taken at the time when a cationic surfactant was added to the core particle dispersion in Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the drawings. The embodiment described below is merely one example of a typical embodiment of the present invention, and the scope of the present invention should not be construed as being narrow.
[0016] <1. Hollow inorganic particles 1> 1 is a cross-sectional image diagram showing an example of the cross-sectional structure of a hollow inorganic particle 1 according to the present technology. The hollow inorganic particle 1 according to the present invention is characterized in that it comprises an outer shell 11 and a hollow 12, and the hollow 12 is present at approximately the center of the hollow inorganic particle 1. That is, the thickness of the outer shell 11 is approximately uniform. Specifically, the ratio of the thinnest part of the outer shell 11 to the thickest part of the outer shell 11 is 0.80 or more.
[0017] The thinnest part of the outer shell 11 / thickest part of the outer shell 11 of the hollow inorganic particle 1 according to the present technology can be appropriately designed depending on the purpose. In particular, in the present technology, the thinnest part of the outer shell 11 / thickest part of the outer shell 11 of the hollow inorganic particle 1 is preferably 0.80 or more, more preferably 0.85 or more, and even more preferably 0.90 or more.
[0018] By setting the ratio of the thinnest part of the outer shell 11 to the thickest part of the outer shell 11 of the hollow inorganic particle 1 according to the present technology to 0.80 or more, the thickness of the outer shell 11 becomes almost uniform and the strength is increased.
[0019] In the prior art, there are techniques for making the porosity and shell thickness uniform among each particle in a hollow particle group, but the present technology is characterized in that the thickness of the shell 11 of each particle is made uniform.
[0020] If the hollows 12 are formed unevenly, the thickness of the shell 11 becomes non-uniform, which may cause problems such as breakage of thin parts of the shell 11 or holes being formed in the particles, but the hollow inorganic particles 1 according to the present technology have high strength because the thickness of the shell 11 is almost uniform. Therefore, the particles are characterized in that they are less likely to be broken even if an external force is applied to them by stirring or a roll mill when they are mixed with other materials such as resin.
[0021] The particle outer diameter L1 of the hollow inorganic particles 1 according to the present technology can be appropriately designed depending on the purpose. In particular, in the present technology, the average particle outer diameter L1 of the hollow inorganic particles 1 is preferably 0.05 to 5 μm, more preferably 0.1 to 3 μm, and further preferably 0.5 to 2 μm.
[0022] By setting the particle outer diameter L1 of the hollow inorganic particles 1 according to the present technology to 0.05 μm or more, the ratio of particles that are not aggregated and are dispersed in the state of primary particles increases. Also, by setting the particle outer diameter L1 of the hollow inorganic particles 1 according to the present technology to 5 μm or less, it becomes possible to increase the particle packing rate when mixed with other materials such as resin, and it is possible to fully exert the intended effects such as low dielectric constant and low refractive index.
[0023] The particle inner diameter L2 and particle outer diameter L1 of the hollow inorganic particles 1 according to the present technology can be appropriately designed depending on the purpose. In particular, in the present technology, the particle inner diameter L2 / particle outer diameter L1 is preferably 0.55 to 0.93, more preferably 0.58 to 0.89, and further preferably 0.63 to 0.85.
[0024] By setting the particle inner diameter L2 / particle outer diameter L1 of the hollow inorganic particles 1 according to the present technology to 0.55 or more, a sufficient air layer can be created in the material to be kneaded, and as a result, the intended effects such as a low dielectric constant and a low refractive index can be fully exhibited. In addition, by setting the particle inner diameter L2 / particle outer diameter L1 of the hollow inorganic particles 1 according to the present technology to 0.93 or less, the thickness of the outer shell can be prevented from becoming thin, and the strength of the particles can be improved.
[0025] The CV value (coefficient of variation of particle size distribution) of the hollow inorganic particles 1 according to the present technology is not particularly limited as long as it does not impair the effects of the present technology. In particular, in the present technology, the CV value of the hollow inorganic particles 1 is preferably 20% or less, more preferably 15% or less, and further preferably 10% or less.
[0026] When the CV value of the hollow inorganic particles 1 according to the present technology is 20% or less, the proportion of particles larger than the average particle outer diameter is small, making the material suitable for applications in which the inclusion of coarse particles is undesirable.
[0027] In the present technology, the CV value is a value calculated by the following formula. CV value (%)={[Standard deviation of particle outer diameter (μm) / [Average particle outer diameter (μm)]×100
[0028] The sphericity of the hollow inorganic particles 1 according to the present technology is not particularly limited as long as it does not impair the effects of the present technology. In particular, in the present technology, the sphericity of the hollow inorganic particles 1 is preferably 0.8 or more, and more preferably 0.9 or more.
[0029] When the hollow inorganic particles 1 according to the present technology have a sphericity of 0.8 or more, the fluidity of the particles is increased when mixed with other materials such as resin, and an increase in viscosity can be suppressed.
[0030] In the present technology, the sphericity is a value calculated by the following formula. Sphericity = [minor diameter of particle outer diameter] / [major diameter of particle outer diameter]
[0031] The water absorption rate of the hollow inorganic particles 1 according to the present technology is not particularly limited as long as it does not impair the effects of the present technology. In particular, in the present technology, the water absorption rate of the hollow inorganic particles 1 is preferably less than 2%, more preferably less than 1%, and further preferably less than 0.5%.
[0032] When the water absorption rate of the hollow inorganic particles 1 according to the present technology is less than 2%, the amount of water absorbed by the hollow inorganic particles 1 can be reduced, and the effect of water on the physical properties of the material to be kneaded can be reduced.
[0033] In this technology, the water absorption rate is the rate of weight increase when left standing at 30 degrees and 90% RH for 48 hours.
[0034] The material forming the outer shell 11 of the hollow inorganic particle 1 according to the present technology is not particularly limited, and can be formed from a material that can be used for general hollow inorganic particles. In particular, in the present technology, the outer shell 11 of the hollow inorganic particle 1 is preferably formed from silica or organopolysiloxane, and more preferably from organopolysiloxane. The organopolysiloxane layer is in a porous state during combustion in the core particle removal step described below, and has the effect of allowing generated gas to escape easily and making the thick outer shell 11 less likely to crack. In addition, a dense silica outer shell 11 can be formed by further treating at a high temperature thereafter.
[0035] Moreover, the shell 11 of the hollow inorganic particle 1 according to the present technology is preferably formed of a high-purity material that does not contain impurities. That is, the shell 11 of the hollow inorganic particle 1 is preferably formed of a material that does not contain metal elements or halogen elements other than the components that constitute the hollow inorganic particle 1.
[0036] The hollow inorganic particles 1 according to the present technology may be a mixture of two or more types of hollow inorganic particles 1 having different average particle sizes. The presence of two or more types of particle sizes can improve the particle packing rate and the proportion of air spaces when kneaded into materials such as resins and ceramics. As a result, the desired effects such as low dielectric constant and low refractive index can be fully achieved.
[0037] Specifically, for example, the proportion of hollow inorganic particles A having an average particle outer diameter of 0.1 to 5 μm can be less than 80% by weight of the total, and the proportion of hollow inorganic particles B having an average particle outer diameter smaller than that of hollow inorganic particles A can be more than 20% by weight of the total.
[0038] The hollow inorganic particles 1 according to the present technology may have their surfaces treated with a resin, a silane coupling agent, or the like for the purpose of improving flowability and suppressing an increase in viscosity when mixed with other materials such as resin.
[0039] The above-described hollow inorganic particles 1 according to the present technology are not particularly limited in use, and can be applied to various general uses of hollow inorganic particles 1. The hollow inorganic particles 1 according to the present technology can be suitably used, in particular, as particles for adjusting dielectric constant.
[0040] <2. Method for producing hollow inorganic particles 1> 2 is a flow diagram of a method for producing hollow inorganic particles 1 according to the present technology. The method for producing hollow inorganic particles 1 according to the present technology is a method that performs at least a coating step S1 and a core particle removing step S2. In addition, in the present technology, it is also possible to perform a core particle dispersion liquid preparation step S3 as necessary. Each step will be described in detail below in chronological order.
[0041] (1) Core particle dispersion preparation process S3 The core particle dispersion preparation step S3 is a step of preparing a core particle dispersion by stirring and mixing the core particles and water. In the core particle dispersion preparation step S3, other additives can also be added as necessary.
[0042] The core particles that can be used in the present technology are not particularly limited as long as they do not impair the effects of the present technology, and any core particles that can be used in the production of general hollow inorganic particles can be freely selected and used. For example, particles made of organic polymers such as polymethyl methacrylate (PMMA), polymethyl acrylate (PMA), polystyrene (PS), polyethylene (PE), polypropylene (PP), polyurethane (PU), polyimide (PI), polyvinyl chloride (PVC), ethylene-vinyl acetate copolymer (EVA), phenolic resin (PF), melamine resin (MF), epoxy resin (EP), polyester resin (PEs), and divinylbenzene polymer can be mentioned.
[0043] The core particles that can be used in the present technology are preferably spherical. The average particle outer diameter can be freely designed according to the desired hollow size. In the present technology, the average particle outer diameter of the core particles is preferably 0.04 to 5.8 μm, more preferably 0.08 to 3.5 μm, and even more preferably 0.4 to 2.4 μm.
[0044] By making the average particle outer diameter of the core particles 0.04 μm or more, the ratio of particles that are not aggregated and are dispersed in the state of primary particles increases. Also, by making the average particle outer diameter of the core particles 5.8 μm or less, it becomes possible to increase the particle packing rate when mixed with other materials such as resin, and the intended effects such as low dielectric constant and low refractive index can be fully exhibited.
[0045] Any additive can be used in the core particle dispersion liquid depending on the purpose. Additives that can be used in the core particle dispersion liquid are, for example, used for the purpose of dispersing the core particles in a solvent. These additives are not particularly limited as long as they do not impair the effects of the present technology, and general additives can be freely selected and used. Examples of additives that can be used in the core particle dispersion liquid include polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), hydroxyethyl cellulose (HEC), polyethylene glycol (PEG), sodium dodecyl sulfate (SDS), carboxymethyl cellulose (CMC), polystyrene sulfonic acid (PSS), polyvinyl sulfate (PVS), polyacrylic acid (PAA), and polymethacrylic acid (PMA).
[0046] The solvent and additives used in synthesizing the core particles may be used as they are. In particular, it is preferable that the dispersant and emulsifier used in the synthesis are added in order to stably disperse the core particles in the solvent. Examples of the method for synthesizing particles using a solvent and additives include dispersion polymerization, soap-free polymerization, emulsion polymerization, swelling seed polymerization, and membrane emulsification.
[0047] In addition, a commercially available resin particle dispersion can be used as the core particle dispersion. The dispersion medium is not particularly limited as long as it does not impair the effects of the present technology, and can be freely selected and used. Examples include water, alcohols such as methanol, ketones such as methyl ethyl ketone, glycols such as ethylene glycol, and glycol ethers such as 1-methoxy-2-propanol. Among these, since water is used as a solvent during synthesis in the present technology, it is desirable to select water as the dispersion medium.
[0048] (2) Covering process S1 The coating step S1 is a step of coating the core particles with a silicone-based compound. In the coating step S1, a dispersant addition step S11, a surfactant addition step S12, a catalyst addition step S13, and a silicone-based compound addition step S14 are performed. In the method for producing hollow inorganic particles 1 according to the present technology, the coating step S1 is characterized in that the dispersant addition step S11 and the surfactant addition step S12 are performed in this order.
[0049] (2-1) Dispersant Addition Step S11 The dispersant adding step S11 is a step of adding a dispersant to the core particle dispersion prepared in the core particle dispersion preparing step S3.
[0050] The dispersant that can be used in the present technology is not particularly limited as long as it does not impair the effects of the present technology, and dispersants that can be used in the production of general hollow inorganic particles can be freely selected and used. For example, nonionic surfactants such as polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), hydroxyethyl cellulose (HEC), and polyethylene glycol (PEG), and anionic surfactants such as sodium dodecyl sulfate (SDS), carboxymethyl cellulose (CMC), polystyrene sulfonic acid (PSS), polyvinyl sulfate (PVS), polyacrylic acid (PAA), and polymethacrylic acid (PMA) can be mentioned. Among these, in the present technology, nonionic surfactants are particularly preferred, and it is more preferred to use polyvinyl alcohol (PVA). The use of nonionic surfactants is preferred in that they do not promote particle aggregation even when used in combination with a cationic surfactant. Furthermore, the hydrophilic group contained in polyvinyl alcohol (PVA) is more preferred because it interacts with silanol groups.
[0051] The concentration of the dispersant in the core particle dispersion after the dispersant addition step S11 is not particularly limited as long as it does not impair the effects of the present technology, but is preferably 1 g / L or more. By setting the concentration of the dispersant in the core particle dispersion in this range, coalescence of the particles can be prevented.
[0052] (2-2) Surfactant addition step S12 The surfactant addition step S12 is a step of adding a cationic surfactant to the core particle dispersion liquid after the dispersant addition step S11. In the present technology, by using a cationic surfactant, it is possible to obtain particles in which the hollow 12 exists at the center of the hollow inorganic particle and the thickness of the shell 11 is uniform.
[0053] In addition, in the present technology, by carrying out the surfactant addition step S12 after the dispersant addition step S11, it is possible to prevent the particles from coalescing and at the same time increase the cationic surfactant concentration on the particle surface, thereby preventing the core particles from becoming uneven. As a result, it is possible to obtain particles in which the hollow 12 exists at the center of the hollow inorganic particle and the thickness of the shell 11 is uniform.
[0054] The cationic surfactant that can be used in the present technology is not particularly limited as long as it does not impair the effect of the present technology, and cationic surfactants that can be used in the production of general hollow inorganic particles can be freely selected and used. For example, cationic polymer surfactants such as polyethyleneimine (PEI) and polydiallyldimethylammonium chloride (PDDA), and cationic low molecular weight surfactants such as polyvinylamine, tetramethylammonium chloride, and cetyltrimethylammonium bromide can be mentioned. Among these, in the present technology, it is particularly preferable to use polyethyleneimine (PEI) or polydiallyldimethylammonium chloride (PDDA), which are cationic polymer surfactants. By using a cationic polymer surfactant, it becomes easier to adsorb to the particle surface, and the effect of preventing the bias of the core particles is further enhanced.
[0055] The concentration of the cationic surfactant in the core particle dispersion after the surfactant addition step S12 is not particularly limited as long as it does not impair the effects of the present technology, but is preferably 0.05 to 5 g / L. By setting the concentration of the cationic surfactant in the core particle dispersion within this range, it is possible to obtain particles in which the hollow 12 exists at the center of the hollow inorganic particle and the thickness of the shell 11 is uniform.
[0056] (2-3) Catalyst addition step S13 The catalyst addition step S13 is a step of adding, to the core particle dispersion, a substance that serves as a catalyst for the hydrolysis and condensation reaction that proceeds in the silicone compound addition step S14 described below.
[0057] The order of the catalyst addition step S13 is not particularly limited as long as it is performed before or at the same time as the hydrolysis and condensation reaction of the silicone compound described later. That is, it may be performed before, after, or at the same time as the addition step S11, before, after, or at the same time as the surfactant addition step S12, or before or at the same time as the silicone compound addition step S14 described later.
[0058] The catalyst that can be used in the present technology is not particularly limited as long as it does not impair the effects of the present technology, and a catalyst that can be used in the production of general hollow inorganic particles can be freely selected and used. For example, at least one of ammonia and amine can be mentioned. Examples of amines include monomethylamine, dimethylamine, monoethylamine, etc. Among these, it is preferable to use ammonia in the present technology from the viewpoints that it is less toxic, easy to remove from the particles, and inexpensive.
[0059] The amount of catalyst added in the catalyst addition step S13 is not particularly limited as long as it does not impair the effects of the present technology, and can be freely set depending on the purpose.
[0060] (2-4) Silicone compound addition step S14 The silicone-based compound adding step S14 is a step of adding a silicone-based compound to the core particle dispersion liquid after the dispersant adding step S11 and the surfactant adding step S12. In the silicone-based compound adding step S14, a hydrolysis and condensation reaction of the silicone-based compound proceeds on the surfaces of the core particles, so that the surfaces of the core particles are covered with the silicone-based compound.
[0061] Silicone compounds that can be used in the present technology are not particularly limited as long as they do not impair the effects of the present technology, and silicone compounds that can be used in the manufacture of general hollow inorganic particles can be freely selected and used. For example, methyltrimethoxysilane (MTMS), methyltriethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, ethyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-acryloyloxypropyltrimethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, dimethyldimethoxysilane, etc. can be mentioned. By using a trifunctional silicone compound, which contains three alkoxyl groups that form a three-dimensional skeleton and one organic group that induces intermolecular interaction, the thickness of the outer shell 11 of the hollow inorganic particle 1 can be made uniformly thick, and for example, when the hollow inorganic particle 1 is mixed with other materials such as resin, even if an external force is applied to the particle by stirring or a roll mill, it is possible to achieve an effect of making it difficult to break. Among these, it is particularly preferable to use methyltrimethoxysilane (MTMS), which is inexpensive and easily available, in this technology.
[0062] The amount of the silicone-based compound added in the silicone-based compound adding step S14 is not particularly limited as long as it does not impair the effects of the present technology, and can be set depending on the purpose of adjusting the shell 11 of the hollow inorganic particle 1 to a desired thickness.
[0063] In the silicone compound addition step S14, the silicone compound is added in the form of an aqueous solution to the core particle dispersion liquid. The method for preparing the silicone compound aqueous solution is not particularly limited as long as it does not impair the effects of the present technology, and it can be prepared using a general aqueous solution preparation method. For example, the silicone liquid aqueous solution can be prepared by stirring and mixing the silicone compound and water.
[0064] In the silicone compound addition step S14, any additive can be added separately at the same time as the addition of the silicone compound aqueous solution depending on the purpose. Examples of additives that can be used include dispersants such as polyvinyl alcohol (PVA) and polyvinylpyrrolidone added in the dispersant addition step S11, cationic surfactants such as polyethyleneimine (PEI) and polydiallyldimethylammonium chloride (PDDA) added in the surfactant addition step S12, and catalysts such as ammonia and amines added in the catalyst addition step S13. These additives can also be added to the silicone compound aqueous solution in advance and then used in the silicone compound addition step S14.
[0065] The method of adding the aqueous solution of the silicone compound to the core particle dispersion is not particularly limited as long as it does not impair the effect of the present technology, and any method of addition that can be used in the production of general hollow inorganic particles can be freely selected and used. In particular, the dropping method is preferably used in the present technology. By using the dropping method, it is possible to obtain particles with a small CV value (coefficient of variation of particle size distribution) and uniform particle size. In addition, by using the dropping method, it is possible to obtain hollow inorganic particles 1 with a uniform thickness of the outer shell 11 (there is no difference in the thickness of the outer shell 11 between particles), and for example, when the hollow inorganic particles 1 are mixed with other materials such as resin, even if an external force is applied to the particles by stirring or a roll mill, it is possible to exhibit an effect that the particles are less likely to be broken. Furthermore, by using the dropping method, it is possible to prevent the particles from sticking to each other, and the particles are not destroyed during particle crushing and resin kneading, and aggregation after resin kneading can also be prevented.
[0066] When producing hollow inorganic particles 1 having a thin outer shell 11, the hollow inorganic particles 1 having the outer shell 11 with a uniform thickness can be obtained even if the material is added all at once without using the dropwise addition method.
[0067] The rate of dropping the aqueous solution of the silicone compound in the silicone compound addition step S14 can also be freely set as long as it does not impair the effect of the present technology. In particular, in the present technology, in order to prevent denaturation of the aqueous solution of the silicone compound, it is preferable to set the dropping rate so that the addition time of the aqueous solution of the silicone compound is within 24 hours.
[0068] (3) Core particle removal process S2 This is a step of removing the core particles after carrying out the coating step S1. By carrying out the coating step S1, the core particles are in a state of being coated with a silicone-based compound, and by removing the core particles in this state, only the outer shells 11 made of the silicone-based compound remain, and the hollow inorganic particles 1 can be produced.
[0069] The method of removing the core particles in the core particle removing step S2 is not particularly limited as long as it does not impair the effect of the present technology, and any removal method that can be used in the production of general hollow inorganic particles can be freely selected and used. For example, when using core particles with low solvent resistance, a method of removing the core particles using an organic solvent can be selected, and when using core particles that can be removed by heating, a method of removing the core particles by heating or baking can be selected. In the present technology, it is particularly preferable to remove the core particles by baking. By performing baking, the removal of the core particles and the densification of the outer shell 11 layers can be performed simultaneously.
[0070] The firing conditions when removing the core particles by firing can be freely set according to the material of the core particles, etc., as long as the effect of the present technology is not impaired. For example, the firing temperature is preferably set in the range of 150 to 1200°C, and more preferably in the range of either 150 to 400°C or 700 to 1200°C. By setting the firing temperature at 150°C or higher, the core particles can be sufficiently removed. Furthermore, by setting the firing temperature at 1200°C or lower, the occurrence of aggregation due to sintering can be prevented. Furthermore, by setting the firing temperature at either the range of 150 to 400°C or 700 to 1200°C, the water absorption rate of the obtained hollow inorganic particles can be less than 2%.
[0071] Here, when the baking temperature is 150 to 400°C, the shell is organopolysiloxane, which is hydrophobic and therefore has a low water absorption rate.When the baking temperature is 700 to 1200°C, the shell is silica, and high-temperature baking reduces OH groups, resulting in less water adsorption, and therefore the water absorption rate is also low. When the firing temperature is 150 to 400°C, the organopolysiloxane shell is expected to reduce the dielectric constant, reduce the hardness of the particles, and improve compatibility with the resin to be kneaded. On the other hand, when the firing temperature is 700 to 1200°C, the silica shell is expected to suppress the linear expansion coefficient, which is a typical characteristic of silica fillers.
[0072] The atmosphere in the firing furnace may be air, or an inert atmosphere in which the oxygen concentration is adjusted by using an inert gas such as nitrogen or argon. By firing in an inert atmosphere, the core particles undergo thermal decomposition (endothermic reaction), so heat generation can be suppressed. Therefore, even when firing a large amount, cracking of the outer shell 11 layers can be prevented, and temperature control becomes easier.
[0073] When firing in an inert atmosphere, the firing temperature is more preferably set in the range of 150 to 1200° C. By firing in this temperature range, the hardness of the hollow inorganic particles 1 can be easily controlled, the water absorption rate can be made less than 2%, and the productivity can be improved.
[0074] It is also possible to combine the firing in air with the firing in an inert atmosphere. For example, firing in an inert atmosphere can be followed by firing in air. By firing in air, organic components contained in the particles can be removed. EXAMPLES
[0075] The present invention will now be described in further detail with reference to examples. The embodiment described below is merely a representative example of the present invention, and the scope of the present invention should not be construed as being narrow.
[0076] <Experimental Example 1> In Experimental Example 1, the differences in strength and water absorption rate due to differences in the shape of hollow inorganic particles were examined.
[0077] 1. Production of hollow inorganic particles Using a general method for producing hollow inorganic particles, hollow inorganic particles with different shapes shown in Table 1 below were produced. Specifically, polymethylmethacrylate (PMMA) particles were used as an example of core particles, and these PMMA particles were coated with methyltrimethoxysilane (MTMS) as an example of a silicone compound to obtain polymethylsilsesquioxane (PMSO)-coated resin particles. The obtained PMSO-coated resin particles were heated to remove the core particles, and hollow inorganic particles were produced.
[0078] The particle size and shell thickness were measured by the following methods. (1) Particle size The core particles, PMSO-coated resin particles, and hollow inorganic particles were each sampled, and the particle sizes of 70 particles were measured by FE-SEM (JSM-6700F, JEOL Ltd.), and the average particle size, CV value, and sphericity were calculated.
[0079] (2) Thickness of the outer shell After embedding the hollow inorganic particles in embedding resin and hardening, the resin was cut with a microtome, and the cross section of the particle was observed with a FE-SEM (JSM-6700F, JEOL Ltd.) to measure the particle outer diameter, particle inner diameter, the part with the thinnest shell thickness (Min), and the part with the thickest shell thickness (Max). From the measurement results, the "part with the thinnest shell thickness (Min shell thickness) / part with the thickest shell thickness (Max shell thickness)" and "particle inner diameter / particle outer diameter" were calculated for 10 particles, and the maximum and minimum values were discarded to calculate the average values of "shell thickness Min / shell thickness Max" and "particle inner diameter / particle outer diameter" for 8 particles.
[0080] 2. Evaluation (1) Water absorption rate 15 g of hollow inorganic particles dried at 150° C. were left to stand in a constant temperature and humidity chamber at 30° C. and 90% RH for 48 hours, and the water absorption rate was calculated from the change in weight before and after the standing.
[0081] (2) Cracking test A mixture of hollow inorganic particles with a ratio of 10 wt% to epoxy resin (jER828, manufactured by Mitsubishi Chemical Corporation) was prepared and kneaded with a spatula. Next, the kneaded mixture was further rolled three times in a roll mill (tabletop roll mill, manufactured by Kodaira Seisakusho) with a gap adjusted to 0.08 mm to prepare a sample for cracking test. The sample for cracking test was prepared by eluting the epoxy resin components with acetone and then centrifuging the mixture for solid-liquid separation, and this process was repeated to extract only the particles after the cracking test. After the cracking test, 3,000 particles were confirmed by observation with a FE-SEM (JSM-6700F, manufactured by JEOL Ltd.), and the percentage of particles confirmed to be cracked was evaluated. The percentage of cracked particles was evaluated as ◎ when less than 1%, ◯ when 1% or more but less than 5%, △ when 5% or more but less than 10%, and × when 10% or more.
[0082] 3.Results The results are shown in Table 1 below.
[0083] [Table 1]
[0084] As shown in Table 1, the hollow inorganic particles of Comparative Example 1, in which the thinnest part of the outer shell / the thickest part of the outer shell is less than 0.80, showed a cracking test in which the percentage of particles confirmed to be cracked was 10% or more. A cross-sectional micrograph of the hollow inorganic particles of Comparative Example 1 is shown in FIG. 5. On the other hand, the hollow inorganic particles of Examples 1 to 6, in which the thinnest part of the outer shell / the thickest part of the outer shell is 0.80 or more, showed a cracking test in which the percentage of particles confirmed to be cracked was less than 10%. A cross-sectional micrograph of the hollow inorganic particles of Example 1 is shown in FIG. 3, and a cross-sectional micrograph of the hollow inorganic particles of Example 2 is shown in FIG. 4.
[0085] Comparing the Examples, the results of the cracking test were better in Examples 1 to 5, which had a particle inner diameter / particle outer diameter ratio of 0.93 or less, than in Example 6, which had a particle inner diameter / particle outer diameter ratio of 0.95. From these results, it was found that a particle inner diameter / particle outer diameter ratio of 0.93 or less is preferable.
[0086] Furthermore, although not confirmed in the examples, when the particle inner diameter / particle outer diameter ratio is less than 0.55, that is, the outer shell becomes thicker, and it is believed that the strength is improved, but the air layer becomes smaller, so when the objective is a low dielectric constant, a low refractive index, etc., it is believed that it is preferable to set the particle inner diameter / particle outer diameter ratio to 0.55 or more.
[0087] <Experimental Example 2> In Experimental Example 2, it was verified how differences in the manufacturing method of hollow inorganic particles affect the manufactured hollow inorganic particles.
[0088] 1. Production of hollow inorganic particles <Examples 7 and 8> (1) Preparation of core particle dispersion As an example of core particles, polymethyl methacrylate (PMMA) particles having the average particle size and CV value shown in Table 2 were used and mixed with water by stirring to obtain a core particle dispersion having the concentration shown in Table 2.
[0089] (2) Preparation of an aqueous solution of silicone compounds As an example of a silicone-based compound, a polymethylsilsesquioxane (PMSO) coating solution was prepared by stirring the amount of methyltrimethoxysilane (MTMS) shown in Table 2 and the amount of water shown in Table 2 at 40°C for 1 hour.
[0090] (3) Addition of dispersant To the core particle dispersion in an amount shown in Table 2, water in an amount shown in Table 2 and a 5% PVA aqueous solution as an example of a dispersant in an amount shown in Table 2 were added, and the mixture was stirred at 30° C. for 10 minutes.
[0091] (4) Addition of surfactants and catalysts To the core particle dispersion to which PVA had been added, a 20% aqueous solution of polydiallyldimethylammonium chloride (PDDA) or a 20% aqueous solution of polyethyleneimine (PEI) in the amount shown in Table 2 as an example of a cationic surfactant, and 1N aqueous ammonia in the amount shown in Table 2 as an example of a catalyst were added.
[0092] (5) Addition of silicone compounds and coating with silicone compounds The PMSO coating solution prepared above was added dropwise to the core particle dispersion to which the dispersant, surfactant, and catalyst had been added, over the time shown in Table 2. This allowed the core particles to be coated with PMSO. After the time shown in Table 2 had elapsed from the end of the dropwise addition, the amount of 1N ammonia water shown in Table 2 was added to solidify the PMSO, thereby obtaining PMSO-coated resin particles. The obtained PMSO-coated resin particles were subjected to solid-liquid separation by centrifugation, and washed three times with methanol. The washed PMSO-coated resin particles were naturally dried for two days, and further dried by heating at 110°C.
[0093] (6) Removal of core particles The PMSO-coated resin particles dried as described above were heated in an electric furnace for 6 hours at a temperature shown in Table 2 under an atmosphere shown in Table 2 to obtain hollow inorganic particles from which the core particles in the PMSO-coated resin particles had been removed.
[0094] <Comparative Example 2> Except for not using a cationic surfactant, PMSO-coated particles were obtained in the same manner as in Example 1. When the obtained PMSO-coated particles were fired under the same conditions as in Example 7 to remove the core particles, the particles had exposed voids and were not hollow particles (see FIG. 6).
[0095] <Comparative Example 3> An attempt was made to obtain PMSO-coated particles using the same method as in Example 7, except that the order of adding the dispersant and cationic surfactant was reversed. However, the particles began to aggregate when the cationic surfactant was added (see Figure 7), and monodisperse particles could not be obtained.
[0096] 2. Evaluation (1) Measurement of particle size Using the same method as in Experimental Example 1, the particle sizes of 70 particles were measured, and the average particle size, CV value, and sphericity were calculated.
[0097] (2) Measuring the thickness of the outer shell Using the same method as in Experimental Example 1, "Min. shell thickness / Max. shell thickness" and "inner particle diameter / outer particle diameter" were calculated.
[0098] (3) Water absorption rate The water absorption rate was determined using the same method as in Experimental Example 1.
[0099] (4) Cracking test A crack test was carried out using the same method as in Experimental Example 1.
[0100] 3.Results The results are shown in Table 2 below.
[0101] [Table 2]
[0102] 4. Discussion As shown in Table 2, the hollow inorganic particles of Examples 7 and 8, in which a cationic surfactant was added after the addition of a dispersant in the coating process, had an average particle outer diameter of 0.05 to 5 μm, a ratio of the thinnest part of the outer shell to the thickest part of the outer shell of 0.80 or more, a particle inner diameter / particle outer diameter of 0.55 to 0.93, a water absorption rate of less than 2%, and good results in the cracking test.
[0103] On the other hand, as described above, in Comparative Example 2 in which no cationic surfactant was used, the particles had exposed voids, and hollow particles could not be obtained (see FIG. 6). In addition, in Comparative Example 3 in which the order of adding the dispersant and cationic surfactant was reversed, aggregation occurred in the PMMA particles when the cationic surfactant was added (see FIG. 7), and monodisperse particles could not be obtained. [Explanation of symbols]
[0104] 1: Hollow inorganic particles 11: Outer shell 12:Hollow
Claims
1. a coating step of coating the core particles made of an organic polymer with a silicone-based compound; a core particle removing step of removing the core particles; having In the coating step, a dispersant addition step of adding a nonionic surfactant as a dispersant to the core particle dispersion; a surfactant addition step of adding a cationic polymer surfactant after the dispersant addition step; A method for producing hollow inorganic particles, comprising the steps of:
2. 2. The method for producing hollow inorganic particles according to claim 1, wherein in the coating step, the concentration of the cationic surfactant in the core particle dispersion after the surfactant addition step is 0.05 to 5 g / L.
3. The method for producing hollow inorganic particles according to claim 1 or 2, wherein the dispersant is a hydrophilic polymer.
Citation Information
Patent Citations
Composite particle, hollow particle and their production
JP1994142491A
Precursor of inorganic hollow particles, inorganic hollow particles, method for producing the same, and optical member and optical member article using inorganic hollow particles
JP2010131592A
Method for producing composite silica particle
JP2011126761A
Method for producing hollow inorganic particle, and hollow inorganic particle
JP2011132087A
Low dielectric resin composition
JP2011225756A